2000
DOI: 10.1108/14636646200000015
|View full text |Cite
|
Sign up to set email alerts
|

Time and Confinement: Towards a Common Sense of Socio‐temporality in a Special Hospital

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Cleary and Edwards (1999) found both service users and nurses identified that because nurses are busy, other pressing tasks take time away from relational support. These findings intersect with Chandley (2000) enquiry into the impact of the experience of passage of time in a secure hospital for service users and practitioners; with the time practitioners spend with service users objectified as a commodity. In Looi et al (2016) and colleagues' Swedish study the provision of nursing care based on therapeutic relationships need not be a challenging task, but it takes place in a complex environment with a propensity to make easy things complicated.…”
Section: Theme 3: Environmentmentioning
confidence: 73%
See 2 more Smart Citations
“…Cleary and Edwards (1999) found both service users and nurses identified that because nurses are busy, other pressing tasks take time away from relational support. These findings intersect with Chandley (2000) enquiry into the impact of the experience of passage of time in a secure hospital for service users and practitioners; with the time practitioners spend with service users objectified as a commodity. In Looi et al (2016) and colleagues' Swedish study the provision of nursing care based on therapeutic relationships need not be a challenging task, but it takes place in a complex environment with a propensity to make easy things complicated.…”
Section: Theme 3: Environmentmentioning
confidence: 73%
“…Though the respective caring environments are complex, internationally there are certain common features, spanning US (Shattell et al, 2008) Australia (Cleary & Edwards, 1999), UK (Chandley, 2000;Long et al, 2012;Reavey et al, 2019) and Sweden (Horberg et al, 2012). Cleary and Edwards (1999) found both service users and nurses identified that because nurses are busy, other pressing tasks take time away from relational support.…”
Section: Theme 3: Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Discussing the neglected aspects of sociotemporality in the context of special hospitals, Chandley demonstrates how the functional nature of time within a ward routine is given its own social and moral expression: 'from the patient perspective, even going to bed and waking in the morning is a collective activity'. 35 This neglect of the individual resonates with insights from Goffman into the characteristics of 'total institutions' such as asylums, convents and concentration camps. 36 Where the ethos of the institution is all-embracing, criteria of utility in terms of how the system operates come to predominate so that even simple patient requests (e.g.…”
Section: Rationalitymentioning
confidence: 99%
“…for money or other goods) can become trivialized and marginalized by nursing and administrative staff. 35…”
Section: Rationalitymentioning
confidence: 99%